EKADASA RUDRA CEREMONY IN 1963 AND 1979: POWER RELATION ISSUE IN BALI - Wardhani, Yanuaresti Kusuma (History Department, Faculty of Humanities, University of Jember, 2023)
This article discusses the enactment of Ekadasa Rudra ceremony in 1963 and 1979 in Pura Agung Besakih, Karangasem, Bali. As the greatest Balinese Hindu ceremony held once in a century, the events were substantial and nationally widespread. The noted events in Indonesian history were in 1963 and 1979, it means that the spatial period was less than twenty years. That problem is an interesting topic to discuss. The discussion uses theory of power relation by Foucault and principle in historical research by Kuntowijoyo, these are determining topic, heuristics, source criticism, interpretation, and historiography. The analysis conducts from explaining each moment of Ekadasa Rudra in both years, then the analysis goes on into the discussion of applying theory of power relation to answer the research question. Keywords: Ekadasa Rudra, ceremony, Bali, power relation